2011
DOI: 10.24200/jams.vol16iss0pp23-33
|View full text |Cite
|
Sign up to set email alerts
|

Fish Kill Incidents and Harmful Algal Blooms in Omani Waters

Abstract: Red tide, one of the harmful algal blooms (HABs) is a natural ecological phenomenon and often this event is accompanied by severe impacts on coastal resources, local economies, and public health. The occurrence of red tides has become more frequent in Omani waters in recent years. Some of them caused fish kill, damaged fishery resources and mariculture, threatened the marine environment and the osmosis membranes of desalination plants. However, a number of them have been harmless. The most common dinoflagellat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 24 publications
1
21
0
Order By: Relevance
“…This is similar to Korean waters where large annual blooms of Cochlodinium occurred from 1995 to 2007 and since 2008 there has been a sharp decrease in blooms of this species for unknown reasons (Lee et al 2013). Occasionally the large nitrogen-fixing cyanobacterium Trichodesmium erythraeum, the dinoflagellates, Karenia selliformis and Prorcentrum arabianum and some diatoms also contribute to the blooms (Al-Gheilani et al 2012).…”
Section: Decadal Changes In Harmful Algal Blooms (Habs) Due To Envirosupporting
confidence: 65%
See 1 more Smart Citation
“…This is similar to Korean waters where large annual blooms of Cochlodinium occurred from 1995 to 2007 and since 2008 there has been a sharp decrease in blooms of this species for unknown reasons (Lee et al 2013). Occasionally the large nitrogen-fixing cyanobacterium Trichodesmium erythraeum, the dinoflagellates, Karenia selliformis and Prorcentrum arabianum and some diatoms also contribute to the blooms (Al-Gheilani et al 2012).…”
Section: Decadal Changes In Harmful Algal Blooms (Habs) Due To Envirosupporting
confidence: 65%
“…5) and this change occurred about the same time as the decrease in red Noctiluca. More HABs have been observed to occur along the northern area adjacent to the Gulf of Oman possibly because more research has been conducted in this area (Thangaraja et al 2007;Al-Azri et al 2012;Al-Gheilani et al 2012). Another plausible explanation is that bloom development is initiated in the Arabian Gulf and then cells are exported into the Gulf of Oman where further growth occurs.…”
Section: Decadal Changes In Harmful Algal Blooms (Habs) Due To Enviromentioning
confidence: 99%
“…Data on sardine landings were complemented by the monthly frequency of fi sh kill incidents and algal blooms along the Omani coast, available from the archives of the Marine Science and Fisheries Research Center (Muscat, Oman) and Al-Gheilani et al (2012).…”
Section: Methodsmentioning
confidence: 99%
“…It is calculated that 383 million fish have lost their lives due to hypoxia along the Texas coast during the fifty years [34]. Over $2.2 billion losses have been estimated by eutrophication-related practices every year [35] and 3000 tuna fish were killed by hypoxia in Kharan Bandar in Oman water in 2004 [36]. The United States Environmental Protection Agency [37] reported that eutrophication damages tourism and recreation, commercial fishing, property values, and human health.…”
Section: Hypoxiamentioning
confidence: 99%